Lead(II)-Selective Coated Graphite Electrode Based on Benzo-18-crown-6 - Ghorbani, Somayeh; Hossein Rounaghi, Gholam; Tarahomi, Somayeh; Mohajeri, Massoumeh (Asian Journal of Chemistry, 2012)
A lead(II)-selective coated graphite electrode based on benzo-18-crown-6 (B18C6) was prepared. This electrode with the membrane composition of 20 % dioctylphthalate, 55 % poly(vinyl chloride), 20 % carbon powder and 4 % benzo-18-crown-6, exhibited a near Nernstian response toward Pb(II) cation over a concentration range 1.0 ×10-5 to 1.0 ×10-1 M with a slope of 28.8 mV per decade and detection limit of 5.0 ×10-6 M. Furthermore, it showed a response time of 30 s and can be used for 3 months without any divergence in potentials. The useful pH range of this electrode is 1.5-5.0. To assess its analytical applicability, the constructed electrode was successfully applied as an indicator electrode in the potentiometric titration of Pb(II) ion solution with EDTA.